(Re-)Assembling Cultural Studies - Cord, Florian (Culture Unbound, 2022)
This paper proceeds from the assumption that the Anthropocene is characterized by a profound impurity and ‘messiness’. It argues that in order to be able to better tackle the immense complexity of the contemporary world, Cultural Studies needs to be more fully posthumanized, that is, brought into an encounter with the various theoretical formations associated with the nonhuman turn (actor-network theory, new materialism, speculative realism, object-oriented ontology, etc.). Specifically, it proposes the concept of the ‘assemblage’ as an alternative onto-epistemic commitment for Cultural Studies and a very productive hinge for such an encounter. Primarily drawing on the work of the philosopher Manuel DeLanda, the article distils the most important features of this concept and then goes on to explore how it calls for a rethinking and revision of some of the central assumptions and categories of Cultural Studies once it is ‘translated’ into the discursive horizon of the discipline. In particular, the essay, availing itself of a wide range of theoretical resources, investigates how the three key concepts of culture, power, and identity undergo a reconceptualization, one that more strongly opens them up to the nonhuman.